UPAYA ORANG TUA DALAM MENDAMPINGI PEMBELAJARAN DARING ANAK DI SDN TAPEN 2 LEMBEYAN MAGETAN - Muhammad Ridlwan Rifa’I (Institut Agama Islam Riyadhlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2021)
This article aims to determine the role of parents in assisting children's learning at SDN Tapen 2 during the covid-19 pandemic. There are 2 methods used in this case study, namely through interviews with several parents and writers using several types of writing from diaries or online news. The results show that the role of parents in general is as a motivator, educator, carer, and supervisor. In particular, the roles of parents that appear are: motivating to build children's learning enthusiasm, facilitating children's needs, supervising children to keep learning optimally, giving an award so that children do not get bored. The results of the research are also about obstacles and strategies to overcome them, the obstacles are: parents cannot optimally accompany their children because they have to work, lack of parental knowledge of the material, lack of parental knowledge of gadgets. Not all parents can overcome these obstacles, because it takes a long time for parents to understand it. The solution that can be done is to provide encouragement that inspires, consolation and an appreciation.